PENGARUH NILAI TUKAR PETANI SUB SEKTOR TANAMAN PANGAN DAN NILAI TUKAR PETANI SUB SEKTOR PERIKANAN TERHADAP INDEK PEMBANGUNAN MANUSIA DI KABUPATEN ACEH UTARA - Devi Andriyani; Eka Mulia (LPPM Universitas Malikussaleh – Indonesia, 2020)
This study aims to analyze the Effect of Exchange Rate of Farmers in the Food Crop Sub Sector and the Farmers' Exchange Rate of Fisheries in the Human Development Index in North Aceh Regency. The data used in this study are secondary data from 2009-2017. The analysis model of this study uses multiple linear regression. The results of the research partially affect the food crop sector in the Human Development Index in the North Aceh Regency government, the fisheries sector influences the Human Development Index in the North Aceh Regency government. Simultaneously the food crop sector and the fisheries sector influence the Human Development Index in the North Aceh Regency government